2010
DOI: 10.1021/am100370y
|View full text |Cite
|
Sign up to set email alerts
|

Innovative High-Surface-Area CuO Pretreated Cotton Effective in Bacterial Inactivation under Visible Light

Abstract: This study presents the first report on enhanced bacterial inactivation of E. coli by RF-plasma pretreated cotton with high-surface-area CuO powders compared with nonpretreated cotton textiles. The high-surface-area CuO (65 m/g) powder was fully characterized. The E. coli inactivation proceeded in the dark and was accelerated under visible and sunlight irradiation even at very low levels of visible light irradiation. The effect the RF-plasma pretreatment of the cotton on the binding of CuO, applied light dose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…[3][4][5] The TiO 2 was sputtered by direct current magnetron sputtering (DC) on polyethylene as reported out of our laboratory. 4,8 Before sputtering the films, the residual pressure P r in the sputtering chamber was set to P r ¡ 10 24 Pa. The substrate target distance was set at 10 cm.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] The TiO 2 was sputtered by direct current magnetron sputtering (DC) on polyethylene as reported out of our laboratory. 4,8 Before sputtering the films, the residual pressure P r in the sputtering chamber was set to P r ¡ 10 24 Pa. The substrate target distance was set at 10 cm.…”
mentioning
confidence: 99%
“…[1][2][3][4] Several methods are used to prepare TiO 2 thin films, based on sol-gel processing depending on the heat resistant of the selected substrate. Sol-gel processing is the most commercially commonly used method to prepare TiO 2 films 5 but the thickness of the TiO 2 films is not reproducible, they…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hashimoto et al [20] have reported the preparation of the Cu and TiO 2 /Cu films by sol-gel methods presenting bactericide action under visible light. Further colloidal Cu-coated textiles showing antibacterial properties have been prepared and tested in our laboratory [21,22]. The particular interest in Cu-textiles is based on the fact that the porous hydrophilic structure of textiles provides a suitable environment for bacterial growth.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the biocidal property of copper and its oxides is used in the design of polymer materials for biomedical devices, 4 in bactericide textiles 5 and antifouling paints, 6,7 to name a few. The adhesion is the first step of bacterial pathogenesis and depends on the nature of the material surface and the bacteria involved.…”
Section: Introductionmentioning
confidence: 99%